Climate change awareness and adaptation strategies of banana, pineapple, and mango farmers in Northern and Southern Mindanao a qualitative approach - Wahing, Geraliza D.; Romo, Glory Dee A.; Sarmiento, Jon Marx P. (2019)
Climate change has brought changes in climatic patterns, such as increasing temperature, rainfall, and humidity. It has also resulted in adverse effects on the agrarian sector. The Philippines is a top producer and exporter of high-value agricultural commodities such as banana, pineapple, and mango. However, the country ranked third among the most climate change-vulnerable countries in the world. To mitigate the negative effects of climate change, farmers engage in different adaptive measures. The study was conducted to assess the climate change awareness and adaptation strategies of farmers in Northern and Southern Mindanao regions, which are the top producers of tropical exports commodities using qualitative approach. Data from a focused group discussion and personal interviews with 80 respondents using a survey questionnaire were processed using the Nvivo software. The result showed that 69% were aware of climate change. From those who were aware, farmers perceived climate change as warming of temperature, unpredictable shifting weather patterns, increased pest and disease outbreaks, delayed fruiting, low quality of crops, decrease in income, and increased cost farm inputs. The in-depths interviews reveal varied responses on the perception of climate change, effects on crop production, input costs and farm income, adaptation strategies, and allocation of household budget. Based on the results of the qualitative approach, the role of land contract arrangement in providing farmers' access to finance and marketing assistance and enhancement of farmers' perception and level of awareness on climate change are crucial in improving farmers' adaptation strategies.
Keywords: Mindanao studies